THE INTERACTION OF PALLADIUM(II) WITH QUATERNARY AMMONIUM SALT IMMOBILISED ONTO SILICA GEL SURFACE: UDC [543.422.3-76:543.421:543.427.4:543.068.53] + 546.98 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
The adsorption of palladium(II) from diluted solution with tetradecyl ammonium nitrate immobilized onto silica gel (TDAN-SG)  depending on chloride concentration and acidity of aqueous solution was investigated. The isotherm of adsorption of Pd(II) in form of acydo complex [PdCl4]2- onto TDAN-SG has a H1-type. This isotherm is formally described by a Langmuir equation and linearized in the coordinates [C]/a-[C] with amax=13 μmol g-1. The Palladium (II) recoveries from solution due to the formation of ion associate (ТДАН)2[PdCl4] onto modified sorbent surface.
Keywords: sorption, palladium(II), quaternary ammonium salt